2001
DOI: 10.1007/bf02704183
|View full text |Cite
|
Sign up to set email alerts
|

Powder XRD investigations on dotriacontane in mixtures: Phase strength and super lattices

Abstract: Powder XRD investigations on dotriacontane-decane and dotriacontane-decanol mixtures are made. Phase strength, phase separation and formation of superlattices are discussed. The role of tunnel-like defects is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Therefore the scope of the study undertaken by the present authors is wider than the earlier one. 1 Results of powder XRD studies on C32-C16, 2 C32-C10 and C32-C10-ol, 3 and C36-C10 to C36-C18 4 were reported earlier. Powder XRD investigations were also carried out on C32-C12, C32-C14, C32-C18 and C28-C10 to C28-C18 5 systems.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Therefore the scope of the study undertaken by the present authors is wider than the earlier one. 1 Results of powder XRD studies on C32-C16, 2 C32-C10 and C32-C10-ol, 3 and C36-C10 to C36-C18 4 were reported earlier. Powder XRD investigations were also carried out on C32-C12, C32-C14, C32-C18 and C28-C10 to C28-C18 5 systems.…”
Section: Introductionsupporting
confidence: 57%
“…Fall in the average strength of β o phase (figure 5, curves A, B) with increasing chain length of SMOLLENC molecules (and thus decreasing total L tlid ) in the binary mixture, can be seen as direct proof of the model of interaction and the role of TLIDs as proposed earlier. 3 It is also noticed that the strength of unidentified phase U p (figure 5, curves E, F) increases with chain length of SMOLLENC component of the binary mixtures (U p was recognized as due to superlattices 3 ); this aspect can be explained as follows.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations